Tradução e adaptação cultural do Quality of Life in Epilepsy (QOLIE-31) - Silva, Tatiana Indelicato da [UNIFESP] (2006)
INTRODUCTION: Up to the present, there are no validated instruments or studies emphasizing reliability and validity of questionnaires to measure quality of life in epilepsy into Brazilian Portuguese. PURPOSE: This report describes the translation and cross-cultural adaptation of the Quality of Life in Epilepsy-31 (QOLIE-31). CASUISTIC AND METHODS: Thirty patients regularly accompanied with temporal lobe epilepsy related to mesial temporal sclerosis (n = 18) and juvenile myoclonic epilepsy (n = 12) answered the questionnaire. RESULTS: One of the authors (Joyce Cramer) conceded the original English version to Portuguese translation. Later, two independent native English-speaking teachers fluent in Portuguese translated this consensus version back into English. Comparison of the back-translation with the original English version showed only a few discrepancies and the English and Portuguese versions were considered conceptually equivalents. Thirty subjects, 20 (66%) female and 10 (34%) male, mean age of 36 years old answered the questionnaire. Socio-demographic characteristics were: regarding to educational level, 10 (30%) had primary school, 16 (53%) secondary and 4 (17%), higher education. Fourteen (46%) had less than 5 seizures in the last month, 10 (33%) 6-10 and 6 (21%) more than 10. After the patients having answered 30 questionnaires only three (10%) of them hadn't understood question 28, which had to be rewritten. CONCLUSION: QOLIE-31 is one of the most widely instruments used to evaluate quality of life in epilepsy. Brazilian patients easily understood its questions. We believe that after finishing validation of its psychometric properties this instrument will be very helpful to evaluate quality of life of Brazilian people with epilepsy.